Recent advances in the formation, stability, and emerging food application of water-in-oil-in-water double emulsion carriers - Elaine, Elaine; Bhandari, Bhesh; Tan, Chin Ping; Nyam, Kar Lin (Springer, 2024)
Double emulsion consists of two interfacial layers which can encapsulate both hydrophilic and lipophilic substances within a single carrier. Besides encapsulation, double emulsion has also been used to modify the sensorial properties of food products. However, at the same time, double emulsion is susceptible to destabilization under environmental stresses and long-term storage. In this paper, recent articles on double emulsion were critically highlighted in terms of production, composition, and stabilization. With current existing fundamental knowledge about double emulsion, this paper aims to review the utilization of double emulsion for food application to bring potential benefits, stability, and future application. The stability of double emulsion during production and storage was affected by the production method, composition, and temperature control. In terms of food application, double emulsion has been successfully applied in fat-reducing products, food encapsulation, fortification, preservation, edible food packaging, etc. The recent insights in forming stable storage of double emulsion with food-grade emulsifiers have also been discussed in this review paper. In the future, the efforts in mitigating the destabilization behaviour of double emulsion might be beneficial in boosting the applications of double emulsion in bigger markets.